2019
DOI: 10.6007/ijarped/v8-i3/6370
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Analysis of the Effectiveness of Behavioral Cognitive Mentoring: A Case Study of the Mothers of Children with Cerebral Palsy

Abstract: Problem Statement: The births of a new child bring with it the changes to the structure of the family and add up to the responsibilities borne by the parents. Parents wish that they have an ideal natural child. However, the opposite occurs in which sometimes parents have a handicapped child that may affect the family, which then entail parents' suffering from psychological stresses which require specialized assistance provided by specialists and counsellors. This study is aimed to determining the effect of CBT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 46 publications
(20 reference statements)
0
2
0
Order By: Relevance
“…Autism prevalence estimates have grown substantially over the previous two decades, from 4 to 5 out of 10,000 children to current estimates of 1 out of 110 children afflicted by autism (Charman et al, 2001). The rise in autism diagnoses, as well as the resulting rise in autism-positive children, has created a greater demand for instructors to understand and use effective autism-specific training techniques (Al-Smadi & Bakar, 2019). Children with autism are autistic children.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Autism prevalence estimates have grown substantially over the previous two decades, from 4 to 5 out of 10,000 children to current estimates of 1 out of 110 children afflicted by autism (Charman et al, 2001). The rise in autism diagnoses, as well as the resulting rise in autism-positive children, has created a greater demand for instructors to understand and use effective autism-specific training techniques (Al-Smadi & Bakar, 2019). Children with autism are autistic children.…”
Section: Introductionmentioning
confidence: 99%
“…In 2003, the COPSSE, Centre for Personnel Studies and Specific Education, reported that, there is a deficit of special education teachers for impaired kids, notably in the fields of emotion or behaviour, as well as general disabilities, learning impairments, and mild or moderate inadequacies (Hay et al, 2004). Moreover, upbringing a child is one of the most sacred gifts and a tasking endeavour that every parent face (Al-Smadi & Bakar, 2019;Aseri et al, 2022). In Alabama, educators report that they are unfit to teach autist in inclusive environments to children (Norsuhaily Abu Bakar et al, 2021).…”
Section: Introductionmentioning
confidence: 99%